Decentralised estimation of distribution algorithm for parallel pumps based on log-linear model. (28th August 2020) - Qian, Xuegen; Yu, Junqi; Zhao, Anjun; Liu, Qite; Zhang, Rui
Aiming at the problem of centralised optimal scheduling of parallel pumps in central air-conditioning system, a new decentralised estimation algorithm with the log-linear model under a new decentralised control framework is proposed. The random sampling method based on the log-linear probability model is applied to generate the new generation population in the proposed algorithm, and the parameters of the probability model are updated based on the dominant population. In the process of the optimisation, each pump is optimised by exchanging information with neighbouring pumps. Finally, a chilled water circulation system is taken as an object to verify the effectiveness of the proposed algorithm through simulation experiments. The results show that the proposed algorithm is an efficient decentralised optimisation algorithm with good universal and scalability, and it can optimise the running strategy of parallel pumps of the same type to realise the purpose of energy saving.